KARAKTERISTIK PASIEN DAN POLA PENGOBATAN OSTEOARTHRITIS DI RSUP DR. SARDJITO, YOGYAKARTA TAHUN 2013 - , NUR ARINA BT. AHMAD DALIMI, Prof. Dr. Sugiyanto, SU, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
-